2022
DOI: 10.3758/s13421-022-01345-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bilingualism on executive functions when languages are similar: a comparison between Hungarian–Serbian and Slovak–Serbian young adult bilinguals

Abstract: Among the factors argued to contribute to a bilingual advantage in executive function (EF), the combination of languages spoken by the bilingual is often overlooked. In this study, we explored the role of language similarity on memory and EF task by comparing performance of three groups of young adults—Hungarian–Serbian and Slovak–Serbian early balanced bilinguals, and Serbian-speaking monolinguals. Slovak is typologically related to Serbian, which are both Slavic, in contrast to Hungarian, which is Finno–Ugri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…If this explanation is on the right track, it supports the processing complexity effect proposed by Antoniou and Wright (2017), which suggests that learning typologically different languages is more cognitively challenging and thus can lead to greater cognitive improvement. Recent evidence also shows that bilinguals speaking typologically unrelated languages may have more efficient executive functions, particularly attention-switching abilities (Perovic et al, 2023). This focus on attention abilities leads to the next finding in the present study, that is, language learners’ better performance in the Posner cueing attention task.…”
Section: Discussionmentioning
confidence: 99%
“…If this explanation is on the right track, it supports the processing complexity effect proposed by Antoniou and Wright (2017), which suggests that learning typologically different languages is more cognitively challenging and thus can lead to greater cognitive improvement. Recent evidence also shows that bilinguals speaking typologically unrelated languages may have more efficient executive functions, particularly attention-switching abilities (Perovic et al, 2023). This focus on attention abilities leads to the next finding in the present study, that is, language learners’ better performance in the Posner cueing attention task.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al (2011) found a similar executive control benefit for both early and late bilinguals (compared to monolinguals) when nonverbal intelligence and socio-economic status were controlled for, but no effects in alerting or orienting. Others have also reported executive control benefits in bilinguals (compared to monolinguals) in the ANT, reflected in an overall RT advantage (Desideri & Bonifacci, 2018;Perovic et al, 2023) as well as more efficient conflict resolution effects (Desideri & Bonifacci, 2018;Marzecová et al, 2013;Ooi et al, 2018). On the other hand, Markiewicz et al (2023) found a trend towards bilinguals being overall slower in a flanker task, reflected in significantly longer response distribution tails compared to monolinguals.…”
Section: The Impact Of Bilingualism On the Attention Networkmentioning
confidence: 92%
“…Another explanation for this processing advantage aligns with the so-called bilingual advantage in cognitive control, which suggests that bilinguals have better domain-general executive controls than monolinguals because of the long-term practice of language control to inhibit the activation of the irrelevant language and resolve cross-linguistic competition (for example, see Bialystok et al, 2008). In addition, it has been reported that this bilingual cognitive advantage is modulated by linguistic distance, as bilinguals whose languages are linguistically more dissimilar exhibit greater advantage in nonlinguistic executive control tasks (Perovic et al, 2022;Lu et al, 2023). Therefore, it is possible that the processing advantage of the Cantonese group found in the current study is due to better cognitive control abilities, which is caused by the long-term practice of controlling two typologically dissimilar linguistic systems than those of the Chengdu group.…”
Section: The E Ects Of Phonological Similaritymentioning
confidence: 99%